Implementasi Model Project Based Learning (PjBL) melalui Lesson Study untuk Meningkatkan Aktivitas Belajar Fisika Peserta Didik Kelas X - Sunardi Sunardi; Khaerus Syahidi; Eko Septi Mardi (LAMBDA : Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2023)
This research is a classroom action research that aims to examine the implementation of the Problem Based Learning model with Lesson Study to improve the physics problem solving abilities of class X students. This research was conducted in class X MIPA 2 SMAN 3 Selong in the even semester of the 2022/2023 school year with 23 learners. This research was conducted in 2 cycles. Data obtained through observation and interviews. The data obtained were analyzed by calculating the average classical student learning activity. The calculation results show that there is an increase in the percentage of student learning activities in cycle I, namely 13.63% very active, 59.09% active and 27.27% quite active to 77.27% very active and 22.73% active in cycle 2. Thus it can be concluded that the implementation of the Project Based Learning model through Lesson Study can increase students' physics learning activities.